Efektifitas Pemberian Teknik IASTM (Instrument Assisted Lymphatic Drainage) Untuk Meningkatkan Kemampuan Fungsional Pada Penderita Osteoarthritis Knee: Case Report - Fatima Ulin Nikmah; Wahyuni Wahyuni; Ismadi Ismadi (LPPM STIKES Siti Hajar dan Insight Power, 2022)
Osteoarthritis (OA) is a degenerative disease that attacks the joints, especially the knee joint. The cause is the cartilage or cartilage that serves to protect the joints begins to break down and joints occur between the ends of the constituent bones. The effects of osteoarthritis are pain, edema, decreased Range of Motion (ROM) resulting in a decrease in the patient's functional activity. In this study using the case report method with the respondent a housewife (Mrs. E) aged 64 years with knee osteoarthritis dextra. Respondents without crepitus in the knee joint, joint stiffness for less than 30 minutes, tenderness at the edge of the bone, limited movement, and edema around the knee. Patient therapy schedule at the hospital 2 times a week. Provide physiotherapy interventions in the form of Lymphatic Breathing Exercise, Instrument Assisted Lymphatic Drainage (IASTM), exercise therapy (Quadricpes isometric contraction exercise and Hold Relax). Measurements were made to measure edema using a metline, measured by the Numeric Rating Scale (NRS), knee ROM as measured by a goniometer, and functional activity using Western Ontario and Mcmaster University (WOMAC). Measurements were made at each therapy session. After physiotherapy intervention was performed 7 times, the results obtained were a decrease in pain and a decrease in disability scores in Ny. E.Keywords: Knee Osteoarthritis, Instrument Assisted Lymphatic Drainage , Exercise, Functional Ability, Pain